Analysis of Drug and Health Resource Use Before and After COVID-19 Lockdown in a Population Undergoing Treatment for Depression or Anxiety - Lear-Claveras, Ana; Clavería, Ana; Couso-Viana, Sabela; Nabbe, Patrice; Oliván-Blázquez, Bárbara (Frontiers in Psychology, 2022)
Introduction The arrival of the COVID-19 pandemic modified the functions of Primary Care (PC) teams, which were forced to focus their resources on the diagnosis and treatment of SARS-CoV-2 infected patients. The disrupted healthcare of individuals with pre-existing mental disorders (depression or anxiety), as well as the psychological decompensation resulting from the lockdown caused by the COVID-19 pandemic, may have modified the use of drugs and health resources by these patients. The aim of this study is to determine the changes in these parameters, between the 6 months prior to the lockdown (09/14/2019 to 03/15/2020) and the 6 months following its end (05/03/2020 to 11/04/2020), in a population undergoing active treatment for depression or anxiety, according to the electronic clinical record. Materials and Methods Real world data observational study of 110,694 individuals aged >16 years suffering from active or undergoing treatment for depression or anxiety according to the electronic medical records of the Aragon Regional Health Service (Spain). Pharmacological variables [daily dose per inhabitant (DHD) dispensed by pharmacies of: anxiolytics, hypnotics/sedatives, and antidepressants] and variables related to the use of healthcare resources (number of primary and specialized healthcare visits) were considered. Student’s T-tests for paired samples were performed to analyze differences between periods (pre–post). The level of significance was established at 5% (p < 0.05). Results The use of anxiolytic drugs increased as compared to its use over the 6 months prior to the lockdown. In contrast, the consumption of antidepressants was found to decrease. The use of health resources continued to be below pre-pandemic levels, 6 months post-lockdown end. Conclusion Changes in the use of health resources could have a negative impact on the parameters of these diseases. The increase in drug use, especially benzodiazepines, may suggest a worsening of the symptoms during the lockdown and in the subsequent months. It is a worrying sign, which points to the growth of this public health problem and the need for its prevention.